Calcineurin Contributes to the Enhancing Effect of Adenosine on Nerve Growth Factor-Induced Neurite Outgrowth via the Decreased Duration of p38 Mitogen-Activated Protein Kinase Phosphorylation - Yoshikage Muroi; Toshiaki Ishii; Kentarou Teramoto; Masatoshi Hori; Masakazu Nishimura (Elsevier, 2004)
Adenosine enhances nerve growth factor (NGF)-induced neurite outgrowth in PC12 cells. We found that adenosine increases NGF-induced phosphorylation of extracellular signal-regulated kinase (ERK), but decreases the duration of phosphorylation of p38 mitogen-activated protein (MAP) kinase. Therefore, we further examined the involvement of protein phosphatase in these effects of adenosine. FK506, a specific calcineurin inhibitor, inhibited the enhancing effect of adenosine on the NGF-induced neurite outgrowth and increased the duration of p38 MAP kinase phosphorylation without affecting ERK phosphorylation. These results suggest that adenosine decreases the duration of p38 MAP kinase via calcineurin activation, which contributes to the enhancement of NGF-induced neurite outgrowth. Keywords:: PC12 cell, nerve growth factor, p38 mitogen-activated protein kinase, neurite outgrowth, calcineurin